A Review on Role of Microbiome in Obesity and Antiobesity Properties of Probiotic Supplements. (9th May 2019) - Sivamaruthi, Bhagavathi Sundaram; Kesika, Periyanaina; Suganthy, Natarajan; Chaiyasut, Chaiyavat
Abstract : Probiotics are now recognized for several health benefits and they have been recommended as a complementary therapeutic agent for metabolic disorders. Obesity is an altered health condition, which is a resultant of irregular energy intake and energy balance, changes in gut microbiota, and improper diet with the influence of genetic makeup and environmental factors. Several studies revealed the influence of probiotic supplementation on obesity-associated consequences in vitro, in vivo, and in human clinical studies. The current manuscript discussed the factors influencing the occurrence of obesity, the interplay between microbiome and obesity, the effect of the probiotic intervention on the health status of obese people, and possible mechanism of antiobesity activity of probiotics. The literature survey revealed that the antiobese activity of probiotics might be associated with their ability to alter the intestinal microbiota, remodeling of energy metabolism, alter the expression of genes related to thermogenesis, glucose metabolism, and lipid metabolism, and change the parasympathetic nerve activity. Further intense research is necessary to figure out the best probiotic or synbiotic mixture and optimum dosage and duration of the intervention to reduce obesity and prevent the recurring of obese condition.